Kinerja Karyawan Bank Syariah : Evaluasi Faktor-faktor Pengaruhnya - Aprih Santoso; Sail Barodin; M. Hasan Ma'ruf (ITB AAS INDONESIA Surakarta, 2021)
The problem in this research is the decline in the performance of marketing employees of Bank BRI Syariah Semarang due to not being able to achieve the targets that have been charged. The research aims to evaluate the influence of incentive factors, emotional intelligence, organizational commitment and work morale on employee performance. The population as well as the sample in this study were all marketing employees of Bank BRI Syariah Semarang totaling 40 people (census technique). The analytical tool in this study is multiple linear regression. The results show that incentives, emotional intelligence, organizational commitment and work morale partially have a positive and significant effect on the performance of marketing employees of Bank BRI Syariah Semarang and the adjusted R square value in the regression model is 0.628 or 68.6 percent of employee performance can be explained by variations incentive variables, emotional intelligence, organizational commitment and morale while the remaining 31.4 percent is explained by other variables. Keywords: performance, incentives, emotional, commitment, passion